2015
DOI: 10.3892/mmr.2015.3443
|View full text |Cite
|
Sign up to set email alerts
|

Roles of lipoxin A4 receptor activation and anti-interleukin-1β antibody on the toll-like receptor 2/mycloid differentiation factor 88/nuclear factor-κB pathway in airway inflammation induced by ovalbumin

Abstract: Previous studies investigating the role of toll-like receptors (TLRs) in asthma have been inconclusive. It has remained elusive whether the toll-like receptors (TLR2)/mycloid differentiation factor 88 (MyD88)/nuclear factor (NF)-κB signaling pathway is involved in lipoxin A4 (LXA4)-induced protection against asthma. Therefore, the present study investigated whether ovalbumin (OVA)-induced airway inflammation is mediated by upregulation of the TLR2/MyD88/NF-κB signaling pathway, and whether it proceeds via the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Keratinocytes and macrophages are the main source of these NF-κB-dependent cytokines upon UVB radiation [39,40], which are released to control inflammatory response [41]. In a model of ovalbumin-induced asthma, treatment with BML-111 reduces NF-κB activation and the upstream adaptor molecule myeloid differentiation primary response 88 (MyD88) in the lungs and recruited immune cells [42]. Corroborating that data, in a model of psoriasis induced by IMQ, treatment with BML-111 reduced NF-κB activation and other clinical signs such as epidermal erythema, scaling, and thickening of the dorsal skin [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keratinocytes and macrophages are the main source of these NF-κB-dependent cytokines upon UVB radiation [39,40], which are released to control inflammatory response [41]. In a model of ovalbumin-induced asthma, treatment with BML-111 reduces NF-κB activation and the upstream adaptor molecule myeloid differentiation primary response 88 (MyD88) in the lungs and recruited immune cells [42]. Corroborating that data, in a model of psoriasis induced by IMQ, treatment with BML-111 reduced NF-κB activation and other clinical signs such as epidermal erythema, scaling, and thickening of the dorsal skin [22].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that neutrophils and mast cells express the ALX/FPR2 receptor [14,15], it is also possible that BML-111 directly inhibited the chemoattraction of these cells. In fact, at least for neutrophils, it was shown that LXA4 and BML-111 reduce their chemoattraction [13,14,16,20,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…However, native LXA4 is rapidly biosynthesized and inactivated, and so it is necessary to synthesize stable and powerful analogs ( Chiang et al, 2000 ). BML-111, 5(S), 6(R), 7-trihydroxyheptanoic acid methyl ester, is a synthetic ALX agonist, which reportedly inhibits neutrophil recruitment and peripheral inflammation ( Lee et al, 1991 ; Gong J. et al, 2012 ; Li et al, 2013 ; Kong et al, 2015 ). It has been demonstrated that BML-111 exerts anti-inflammatory effects in the cerebral cortex and maintains the integrity of the blood–brain barrier after ischemic stroke ( Hawkins et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…A solution of BML-111 (2 mg/0.5 ml 100% alcohol) was diluted in 2 ml normal saline as an inhalation solution for each patient in the relevant group. Previous studies were used as references for the selection of 5(S),6(R)-LXA 4 methyl ester and BML-111 dosages (17,(28)(29). Pulmicort, an inhaled glucocorticoid budesonide, was obtained from AstraZeneca (London, UK).…”
Section: Patientsmentioning
confidence: 99%
“…A previous study indicated that treatment of allergic eczema in infants with topical 15(R/S)-methyl-LXA 4 decreased eczema severity and duration, and improved patients' quality of life with a similar efficacy to topical corticosteroids (27). LXA 4 exhibits the potential to be a novel therapeutic treatment in asthma (5,28,29). Thus, clinical trials with LXA 4 stable analogs are required to determine its efficacy and safety in the treatment of asthmatic patients.…”
Section: Introductionmentioning
confidence: 99%